Working from home and mental well-being in the EU at different stages of the COVID-19 pandemic: A gendered look at key mediators - Sandra M. Leitner (The Vienna Institute for International Economic Studies (wiiw), 2024)
This paper analyses the relationship between working from home (WFH) and mental well-being at different stages during the first two critical years of the COVID-19 pandemic, when governments repeatedly imposed lockdowns and enacted WFH mandates to contain the spread of the virus. Using data from a representative survey conducted at four different time periods in 2020 (first lockdown, subsequent gradual reopening), 2021 (further lockdown) and 2022 (restrictions widely lifted) in the 27 EU member states, it examines the potentially changing role of several mediators over time, such as work-family conflict, family-work conflict, stability, resilience, isolation, the importance of different support networks, workload, physical risk of contracting COVID-19 at work, and housing conditions. For the first lockdown, it also differentiates by previous WFH experience, in terms of WFH novices and experienced WFH workers. It differentiates by gender, in order to take the potential gendered nature and effect of COVID-19 measures into account. The results show that while there was no direct relationship between WFH and mental well-being, there are several important mediators whose relevance was specific not only to certain stages of the pandemic, but also to previous experience with WFH and gender. Stability is the only mediator that was relevant over the entire two-year pandemic period. Work-family conflict and family-work conflict were only relevant during the first lockdown, while resilience and isolation mattered especially when most of the EU economies had lifted most of their restrictions. Unlike established WFH workers, WFH novices had an advantage during the first lockdown, benefiting from lower family-work conflict and more helpful networks of family and friends. Moreover, our results differ by gender: for females who undertook WFH, important mediators were work-family conflict and family-work conflict. Both were related to adjustments they had to make in work and non-work hours in response to the enforced closure of schools and childcare facilities during the lockdowns, especially during the first. For males who undertook WFH, especially WFH novices, support from networks of family and friends was an important mediator.
Keywords: I10; I31; J81; 330; working from home; mental well-being; COVID-19; structural equation modelling